Endovascular stenting of the ascending aorta for visceral malperfusion in a patient with type A aortic dissection - Karan Garg, MD; Matthew Pergamo, MD; Jeffrey Jiang, MD; Deane Smith, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2023)
A type A aortic dissection is a challenging condition for both cardiothoracic and vascular surgeons. Although open surgery remains the gold standard, there is considerable interest in the use of endovascular techniques for patients who present with malperfusion. We present the case of an unstable 55-year-old man with visceral malperfusion from a type A dissection who was stabilized using an endovascular technique as a bridge to open surgery. A bare metal thoracic endograft was used in the ascending aorta to rapidly restore perfusion. This hybrid approach to the problem of malperfusion in type A dissection could be useful for these patients with complicated cases.